The Impact of Green Behavior and Energy-Saving Practices on Green Economic Growth: Empirical Evidence from the Restaurant Industry in Indonesia - Jayawarsa , Anak Agung Ketut; Saputra, Komang Adi Kurniawan (Universitas Pendidikan Ganesha, 2025)
This research focuses on environmental and energy problems that occur in Indonesia. The high industrial waste generated in business or restaurant businesses needs to be addressed massively in reducing it. This is in line with the government's program to create a common goal, namely a green economy. The research was conducted on a total of 274 restaurant businesses in Bali-Indonesia because this industry uses a lot of electricity and water and contributes plastic and liquid waste. Data collection techniques using a survey with the help of a questionnaire. The research instrument was sent personally using surveyors and online methods. The results obtained from this study indicate that green behavior and energy saving have a significant positive effect on the green economy. The research contribution is aimed at the concept of achieving a green economy in Bali and making firm policies related to environmental protection by paying attention to green behavior and energy saving campaigns. The research implications are aimed at restaurant business practices, namely providing input on efforts that can be made by local governments in overcoming environmental pollution and restaurant waste piles. The approaches taken by the government previously used economic criminology approaches, with the results of this study it is hoped that the government can use psychological and behavioral approaches in efforts to preserve the environment and business sustainability.